2004
DOI: 10.1002/hon.738
|View full text |Cite
|
Sign up to set email alerts
|

The combination of intermediate doses of thalidomide and dexamethasone reduces bone marrow micro‐vessel density but not serum levels of angiogenic cytokines in patients with refractory/relapsed multiple myeloma

Abstract: The aim of the study was the evaluation of anti-angiogenic activity of the combination of intermediate doses of thalidomide and dexamethasone in patients with refractory/relapsed myeloma. Twenty-five patients were included in the study. Microvessel density (MVD) was evaluated in marrow biopsies before and after treatment. Serum levels of vascular endothelial growth factor (VEGF), basic fibroblast growth factor (b-FGF), tumor necrosis factor-alpha (TNF-alpha), which have angiogenic potential and interleukin-6 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
3
22
2
1
Order By: Relevance
“…Increased circulating levels of VEGF and of angiogenin have been previously described in patients with MM [20][21][22] and our results confirm these observations. The effect of circulating VEGF on survival of myeloma patients who received CC was previously reported but the results were conflicting.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increased circulating levels of VEGF and of angiogenin have been previously described in patients with MM [20][21][22] and our results confirm these observations. The effect of circulating VEGF on survival of myeloma patients who received CC was previously reported but the results were conflicting.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of circulating VEGF on survival of myeloma patients who received CC was previously reported but the results were conflicting. 20,23 In our study, circulating VEGF had no prognostic value; this may be due to the reduction of VEGF by novel agent-based therapies, 11,22,24,25 which may override a possible adverse effect of VEGF on prognosis.…”
Section: Discussioncontrasting
confidence: 55%
“…Thirdly, MVD and VEGF tended to decline in responding patients, confirming observations by some, but not all, investigators. [24][25][26] In support of our observation, Du et al and Hatjuharissi et al both reported a significant decline in MVD in patients with myeloma who responded to thalidomide and Kumar et al demonstrated a similar degree of MVD reduction to that seen in our study.…”
supporting
confidence: 91%
“…24,25,[28][29][30][31] One study correlating responses to chemotherapy with VEGF levels demonstrated results different from ours -with lower VEGF levels associated with higher complete or partial responses to chemotherapy and longer survival times.…”
Section: -26mentioning
confidence: 96%
See 1 more Smart Citation